Fastest Route for Public Health Center in Bandung with Dijkstra Algorithm and FP-Growth Recommendation in C++ Programming Language - Kurnia, Andika Eka; Sunaryo, Gregorius Christian; Zamzami, Muhammad Rafi; Melany, Naila; Nugraha, Rafi Nazhmi; Ariyanti, Rahma Dina (Journal of Software Engineering, Information and Communication Technology (SEICT), 2024)
This research addresses the need for efficient public health center access in Bandung. In this case study, the solution to that specific problem is implemented using the C++ programming language. Consequently, extreme programming is chosen as the research methodology. We implemented Dijkstra's algorithm to find the shortest routes and the FP-Growth algorithm to recommend frequently visited health centers based on previous history. By leveraging C++ for its performance advantages, the system maps urban villages and calculates optimal paths. Additional features manage village data, create routes, and display health center information. The combined use of these algorithms enhances navigation and healthcare access in urban settings, though future work should consider real-time traffic conditions.